(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the key determinants of economic growth in developing countries by analyzing both economic and non-economic factors. Economic determinants such as investment, foreign direct investment (FDI), trade openness, technological progress, human capital, fiscal and monetary policies are explored alongside non-economic factors including governance, political stability, geography, and institutional reforms